Formal perovskite solar cell with rubidium acetate doped electron transport layer and preparation method of formal perovskite solar cell

By introducing rubidium acetate doped electron transport layer at the buried interface of perovskite solar cells, rubidium acetate ions are used to improve the crystal quality and interface energy level matching of perovskite films, the problems of interface mismatch and defect accumulation are solved, and efficient power conversion efficiency and stability are achieved.

CN119730548AActive Publication Date: 2025-03-28UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411907582.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Interface mismatch and defect accumulation of buried interfaces in formal perovskite solar cells lead to low power conversion efficiency.

Method used

Rubidium acetate doped electron transport layer is used to introduce rubidium ions and acetate ions in the critical stage of perovskite film growth, improve the crystalline quality of perovskite film, reduce harmful defects, and optimize interface energy level matching.

Benefits of technology

It significantly improves the power conversion efficiency of perovskite solar cells, enhances the crystallinity and stability of the film, and optimizes the carrier extraction and transmission efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730548A_ABST
    Figure CN119730548A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photovoltaic cells, and particularly relates to a formal perovskite solar cell with a rubidium acetate-doped electron transport layer and a preparation method thereof, and the solar cell device structure sequentially comprises an FTO substrate, an electron transport layer, a doped electron transport layer, a perovskite layer, a hole transport layer and a metal electrode layer from bottom to top. The doped electron transport layer is a thin film layer prepared by doping rubidium acetate into a stannic oxide (SnO2) aqueous solution and carrying out spin coating and annealing. According to the invention, rubidium ions and acetate ions are introduced into the bottom-buried interface of the perovskite thin film, the crystallization process of the perovskite thin film is promoted, the crystallization quality of the perovskite thin film is improved, the iodine vacancy defect of the bottom-buried interface is filled, the recombination rate of current carriers is successfully reduced, the energy level matching condition between the electron transport layer and the perovskite layer is optimized, and the performance of the perovskite thin film is improved. Finally, the power conversion efficiency of the formal perovskite solar cell is improved, and a foundation is built for commercial application and further technical development of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic cells, and in particular relates to a formal perovskite solar cell with a rubidium acetate-doped electron transport layer and a preparation method thereof. Background Art

[0002] Perovskite has the characteristics of easy solution preparation and excellent photovoltaic performance. As an excellent optoelectronic material, organic-inorganic hybrid perovskite has many advantages such as adjustable band gap, high light absorption coefficient, low exciton dissociation energy and relatively simple and low-cost preparation process. In the past few years, the efficiency of formal perovskite solar cells has been greatly improved. Perovskite solar cells were first introduced in 2009, when their photoelectric conversion efficiency (PCE) was only 3.8%. After more than ten years of rapid development, the PCE of single-junction perovskite solar cells has exceeded 26%, which is very close to the highest efficiency of single-crystal silicon solar cells, but it is still lower than the Shockley-Queise theoretical limit efficiency of 33.4%. Therefore, it is still necessary to further improve the power conversion efficiency of perovskite solar cells.

[0003] In the structure of perovskite solar cells, the perovskite layer is undoubtedly the key factor that determines the performance of the cell. In addition to optimizing the perovskite light-absorbing layer itself to optimize its quality, the buried interface of the formal perovskite solar cell, that is, the electron transport layer, will also have a significant impact on the morphology, defect generation and continuity of the perovskite film, and thus affect the power conversion efficiency of the device. In particular, it should be pointed out that the inhomogeneity of the perovskite components at the contact of the buried interface will lead to defect accumulation and unexpected non-radiative recombination losses. In addition, although the interface modification at the buried interface does not change the nucleation mechanism of the perovskite, it can significantly prolong the growth process of the perovskite near the buried interface, thereby affecting the subsequent surface recrystallization. This bottom-up modulation of crystallization dynamics will generate larger grains in the formed film while reducing crystal defects. In addition, the energy level mismatch at the buried interface will also have a great impact on the extraction of electron (formal perovskite solar cell) and hole (inverted perovskite solar cell) carriers of perovskite solar cells. It is reported that the height of the interface energy barrier affects the carrier dynamics. When the interface barrier is greater than 0.1eV, it will hinder the extraction of most carriers, thereby causing charge accumulation and recombination losses. Therefore, how to obtain high-quality, high-crystallinity perovskite films and optimize interface energy level matching has become a technical problem to be solved in the preparation of high-efficiency formal perovskite solar cells. Summary of the invention

[0004] The purpose of the present invention is to provide a formal perovskite solar cell with a rubidium acetate-doped electron transport layer and a preparation method thereof in view of the above-mentioned problems existing in the buried interface in the formal perovskite solar cell. By using the method of rubidium acetate-doped electron transport layer, the crystallization quality of the perovskite film is improved, the harmful defects in the perovskite light-absorbing layer are reduced, and the problem of interface energy level mismatch is alleviated, thereby improving the power conversion efficiency of the formal perovskite solar cell.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A formal perovskite solar cell with rubidium acetate doped electron transport layer comprises FTO conductive glass, an electron transport layer, a doped electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode layer deposited in sequence on the FTO conductive glass; the electron transport layer is a tin dioxide (SnO2) layer prepared by a water bath deposition method; the second electron transport layer is a tin dioxide (SnO2) layer prepared by a water bath deposition method; 2 ) The film is prepared by doping rubidium acetate small molecules in aqueous solution and then spin coating and annealing.

[0007] Furthermore, the material of the perovskite light absorbing layer is FA x MA 1-x PbI 3 , where 0 <x<1。

[0008] Furthermore, the hole transport layer comprises Spiro-OMeTAD, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 4-tert-butylpyridine (TBP).

[0009] A method for preparing a formal perovskite solar cell with a rubidium acetate-doped electron transport layer comprises the following steps:

[0010] Step 1, cleaning the FTO conductive glass, and preparing an electron transport layer on the FTO conductive glass by a water bath deposition method;

[0011] Step 2: preparing a doped electron transport layer on the electron transport layer by spin coating, wherein the method is as follows:

[0012] 2.1. Add deionized water to the tin dioxide aqueous dispersion, mix and dilute, and oscillate to evenly mix the two to obtain a tin dioxide aqueous solution A; wherein the tin dioxide aqueous dispersion: deionized water = 5:1;

[0013] 2.2. Adding rubidium acetate as a dopant to the tin dioxide aqueous solution A to obtain tin dioxide aqueous solution B; the concentration of the added rubidium acetate is 0.5-3 mg / mL;

[0014] 2.3, spin coating the tin dioxide aqueous solution B on the electron transport layer obtained in step 2, the spin coating speed is 3000-5000 rpm, the time is 30-40 s, and annealing is carried out at a temperature range of 120-150° C. for 30-40 min to obtain a doped electron transport layer;

[0015] Step 3, respectively preparing a lead iodide precursor solution and a mixed organic salt solution, and sequentially spin-coating the lead iodide precursor solution and the mixed organic salt solution on the doped electron transport layer using a two-step spin coating method, and annealing to obtain a perovskite light absorbing layer;

[0016] Step 4: Spin-coat the hole transport layer on the perovskite light-absorbing layer, deposit the metal electrode, and obtain a formal perovskite solar cell with a rubidium acetate-doped electron transport layer.

[0017] Furthermore, the method for implementing step 1 of preparing an electron transport layer on FTO conductive glass by water bath deposition is as follows:

[0018] 1.1. Prepare solution C by mixing 1.25 mL of HCl solution, 25 ul of thioglycolic acid (TGA), and 100 ml of deionized water;

[0019] 1.2. Add 1250 mg urea and 275 mg SnCl to solution C obtained in step 2.1. 2 ·2H 2 O to prepare solution D;

[0020] 1.3. Immerse the FTO glass obtained in step 1 in solution D obtained in step 2.2 and heat in an oven at 90°C for 4 hours;

[0021] 1.4, deposit SnO in water bath obtained in step 2.3 2 The FTO glass was cleaned with deionized water in an ultrasonic oscillator for 10 min, dried, and then placed on a hot plate at 170°C for 60 min to obtain an electron transport layer.

[0022] Furthermore, the implementation method of step 3 includes the following steps:

[0023] 3.1. Add a mixed solvent to lead iodide, wherein the mixed solvent is composed of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 9:1. Heat and stir at 60-80°C until dissolved to prepare a lead iodide precursor solution;

[0024] 3.2. Weigh 180-184 mg FAI, 12.8 mg MAI, and 9-9.5 mg MACL and dissolve them in 1 mL isopropanol to prepare a mixed organic salt solution;

[0025] 3.3. Spin-coat the prepared lead iodide precursor solution onto the obtained doped electron transport layer at a rotation speed of 1200-1800 rpm for 30 s, and anneal at 70°C to obtain a lead iodide film; spin-coat the prepared mixed organic salt solution onto the obtained lead iodide film at a rotation speed of 1800-2000 rpm for 30 s, and then transfer to an environment with a relative humidity of 30%-40%, and anneal at 150°C to obtain a perovskite light absorbing layer.

[0026] Furthermore, the method for preparing the hole layer in step 4 is:

[0027] 4.1. Weigh 500-520 mg of LiTFSI and add 1 mL of acetonitrile. Stir at room temperature until dissolved to prepare a LiTFSI solution.

[0028] 4.2. Weigh 70-75 mg of Spiro-OMeTAD, add 1 mL of chlorobenzene and 25-30 uL of TBP and 15-18 uL of the LiTFSI solution obtained in step 4.1, and stir at room temperature until dissolved to prepare a Spiro-OMeTAD solution;

[0029] 4.3. Spin-coat the Spiro-OMeTAD solution obtained in step 4.2 onto the perovskite light-absorbing layer at a rotation speed of 3000-5000 rpm for 30-40 seconds to obtain a hole transport layer.

[0030] The present invention achieves a significant improvement in battery performance by adding a doped electron transport layer between the electron transport layer and the perovskite light absorbing layer and introducing rubidium acetate small molecules into the doped transport layer. In the critical stage of perovskite film growth, rubidium ions play a vital role between the perovskite film and the underlying interface. These rubidium ions become nucleation centers, effectively catalyzing the crystallization process of the perovskite film. This process not only greatly increases the grain size of the perovskite film, but also significantly improves the overall crystallinity of the film. Moreover, this improvement is effective in reducing the harmful excess PbI in the film. 2 The effects are significant in two aspects, which can not only optimize the performance of perovskite films, but also enhance the device stability of perovskite solar cells. Second, acetate has a stronger coordination ability than halogen ions, which can more efficiently fill the iodine vacancy defects at the perovskite buried interface, thereby inhibiting carrier recombination and improving the open circuit voltage and fill factor. This can significantly reduce the most common and harmful lattice defects in the film, further improving the quality and stability of the film.

[0031] In addition, by adding a doped electron transport layer doped with rubidium acetate between the electron transport layer and the perovskite light absorption layer, the energy level matching between this layer and the perovskite layer was successfully optimized. This optimization significantly reduces the energy level barrier of the interface carriers, facilitating the rapid extraction and transmission of carriers. In this way, the transmission efficiency of carriers between the perovskite layer and the electron transport layer is greatly improved, which directly affects the overall performance improvement of solar cells.

[0032] In summary, the present invention promotes the crystallization process of the perovskite film by introducing rubidium ions and acetate ions at the buried interface of the perovskite film, effectively improves the crystallization quality of the film, reduces the excess PbI2 in the perovskite film, fills the iodine vacancy defects at the buried interface, thereby reducing the recombination of carriers, and optimizes the energy level matching between the electron transport layer and the perovskite layer, thereby improving the power conversion efficiency of the formal perovskite solar cell, laying a solid foundation for its commercial application and further technological development. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a schematic diagram of the solar cell structure of Example 1;

[0034] Figure 2 This is a schematic diagram of the solar cell structure of Comparative Example 1;

[0035] Figure 3 The morphology of the perovskite films of Example 1 and Comparative Example 1 under a scanning electron microscope (SEM); wherein (a) is the perovskite film obtained in Comparative Example 1, and (b) is the perovskite film obtained in Example 1;

[0036] Figure 4 X-ray diffraction (XRD) patterns of the perovskite films obtained in Example 1 and Comparative Example 1;

[0037] Figure 5 Graphs of photoluminescence spectra (PL) of the perovskite films obtained in Example 1 and Comparative Example 1;

[0038] Figure 6 The device JV curve diagram of the formal perovskite solar cell obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in combination with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Unless otherwise defined, the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0042] Example 1

[0043] This embodiment provides a method for preparing a formal perovskite solar cell with a rubidium acetate-doped electron transport layer:

[0044] Step 1: Clean the substrate:

[0045] In this embodiment, fluorine-doped indium tin oxide (FTO) glass is selected as the substrate; first, acetone and anhydrous ethanol are used for ultrasonic cleaning for 15 minutes each, the washed substrate is blown dry with a nitrogen gun and stored in a dry environment, and a UV-ozone cleaning device is used for 30 minutes before use.

[0046] Step 2: Preparation of electron transport layer:

[0047] In this embodiment, a tin dioxide electron transport layer is deposited on the FTO conductive glass by a water bath deposition method, and the preparation steps are as follows:

[0048] Step 2.1: Prepare solution C by mixing 1.25 mL of HCl solution, 25 ul of thioglycolic acid (TGA), and 100 ml of deionized water;

[0049] Step 2.2: Add 1250 mg urea and 275 mg SnCl to solution C obtained in step 2.1. 2 ·2H 2 O to prepare solution D;

[0050] Step 2.3: immerse the FTO glass prepared in step 1 in solution D obtained in step 2.2 and heat in an oven at 90°C for 4h;

[0051] Step 2.4: Deposit SnO in a water bath 2 The FTO glass was cleaned with deionized water in an ultrasonic oscillator for 10 min, dried, and then placed on a hot plate at 170°C for 60 min to obtain an electron transport layer.

[0052] Step 3: Preparation of doped tin dioxide electron transport layer:

[0053] Step 3.1: Add deionized water to the tin dioxide aqueous dispersion to mix and dilute, wherein the tin dioxide aqueous dispersion: deionized water = 5:1, and oscillate to prepare a diluted tin dioxide aqueous solution A;

[0054] Step 3.2: Adding a doping agent, rubidium acetate, to the obtained tin dioxide aqueous solution A, wherein the concentration of rubidium acetate is 0.5 to 3 mg / mL, to obtain a tin dioxide aqueous solution B;

[0055] Step 3.3: Then, spin-coat the tin dioxide aqueous solution B on the electron transport layer obtained in step 2 at a spin-coating speed of 3000-5000 rpm for 30-40 seconds, and anneal at a temperature range of 120-150° C. for 30-40 minutes to obtain a doped electron transport layer;

[0056] Step 4: Preparation of perovskite light absorbing layer:

[0057] Step 4.1: Weigh 691.5 mg of lead iodide and dissolve it in 1 mL of a mixed solvent and stir at 70° C. for 6 h. The mixed solvent is composed of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 9:1 to prepare a lead iodide precursor solution;

[0058] Step 4.2: Weigh 180-184 mg FAI, 12.8 mg MAI, and 9-9.5 mg MACL and dissolve them in 1 mL isopropanol. Stir at room temperature until dissolved to prepare a mixed organic salt solution.

[0059] Step 4.3: Spin-coat the prepared lead iodide precursor solution onto the doped electron transport layer at a rotation speed of 1200-1800 rpm for 30 seconds, and anneal at 70°C to obtain a lead iodide film; spin-coat the prepared mixed organic salt solution onto the obtained lead iodide film at a rotation speed of 1800-2000 rpm for 30 seconds, then transfer to an environment with a relative humidity of 30%-40%, and anneal at 150°C to obtain a perovskite light absorbing layer.

[0060] Step 5: Preparation of hole transport layer:

[0061] Step 5.1: Weigh 520 mg of LiTFSI and add 1 mL of acetonitrile, and stir at room temperature until dissolved to prepare a LiTFSI solution;

[0062] Step 5.2: Weigh 72.3 mg of Spiro-OMeTAD, add 1 mL of chlorobenzene and 30 uL of TBP and 18 uL of the LiTFSI solution obtained in step 5.1, and stir at room temperature until dissolved to prepare a Spiro-OMeTAD solution;

[0063] Step 5.3: Spin-coat the Spiro-OMeTAD solution obtained in step 5.2 onto the perovskite light-absorbing layer at a rotation speed of 3000 to 5000 rpm for 30 to 40 seconds to obtain a hole transport layer.

[0064] Step 6: Preparation of metal electrodes:

[0065] In this embodiment, gold is selected as the metal electrode, and the preparation method is: 120nm of gold is deposited on the surface of the electron transport layer by vacuum thermal evaporation through a mask. Figure 1 The completed formal perovskite solar cell shown.

[0066] Comparative Example 1

[0067] This comparative example provides a method for preparing a formal perovskite solar cell. The process is different from that of Example 1 in that the process of adding rubidium acetate as a dopant in step 3.2 is not included, and the tin dioxide aqueous solution obtained in step 3.1 is directly spin-coated on the substrate. The other steps are exactly the same. The structure is as follows: Figure 2 shown.

[0068] The above-mentioned Example 1 and Comparative Example 1 are analyzed and tested below:

[0069] The perovskite films obtained in Example 1 and Comparative Example 1 were analyzed by SEM, and the results are as follows: Figure 3 As shown, Figure 3 (a) The perovskite film obtained in Example 1, Figure 3 (b) The perovskite film obtained in Example 1. Compared with Comparative Example 1, after rubidium acetate was added to the spin-coated tin dioxide electron transport layer in Example 1, the perovskite grain size was significantly increased. In addition, compared with Comparative Example 1, the white byproduct PbI 2 The number of PbI 2 The reaction becomes perovskite, which means it can improve the crystal quality.

[0070] XRD analysis was performed on the perovskite films obtained in Example 1 and Comparative Example 1, respectively. Figure 4 It can be seen that the XRD spectrum represents PbI 2 The characteristic peak at 12.7° of the perovskite film is significantly reduced after rubidium acetate is doped into the electron transport layer, indicating that the PbI 2 The content of PbI in the perovskite film is reduced, indicating that the acetate ions and rubidium ions at the buried interface can effectively regulate the PbI 2 At the same time, the characteristic peak position of Example 1 and Comparative Example 1 at the 14.2° position representing the perovskite (100) crystal plane is the same, and no shift phenomenon occurs, indicating that the addition of acetate ions and rubidium ions to the buried interface does not affect the composition and structure of the perovskite film grown thereon.

[0071] The PL spectrum analysis of the perovskite films obtained in Example 1 and Comparative Example 1 was performed respectively. Figure 5 It can be seen that the characteristic peak intensity of the perovskite film obtained in Example 1 at 750-850nm is much lower than that in Comparative Example 1, which indicates that the acetate ions and rubidium ions at the buried interface can reduce the non-radiative recombination in the perovskite film. It also indicates that the rubidium acetate-doped electron transport layer has a stronger ability to extract electrons, and the energy level of the rubidium acetate-doped electron transport layer is more matched with the perovskite light absorption layer.

[0072] Photovoltaic tests were performed on the formal perovskite solar cells obtained in Example 1 and Comparative Example 1, and the effective active area was 0.0491 cm 2 The test conditions are standard simulated sunlight AM1.5 and temperature 25℃. The obtained JV curve is shown in the figure below. Figure 6 As shown in Table 1, the photovoltaic parameters show that the open circuit voltage of the formal perovskite solar cell obtained in Example 1 is 1.07V and the short circuit current is 25.37mA / cm 2 , the filling factor is 79.78%, and the energy conversion efficiency is 21.66%; compared with comparative example 1, the open circuit voltage and the filling factor of embodiment 1 are greatly improved, and the photoelectric conversion efficiency is thus improved by nearly 12.6% compared with comparative example 1, which indicates that the rubidium acetate-doped electron transport layer significantly optimizes the photovoltaic performance of the formal solar cell device.

[0073] Table 1 Comparison of performance of perovskite solar cells between Example 1 and Comparative Example 1

[0074]

[0075]

[0076] The above embodiments are intended to provide a better understanding of the present invention, but are not limited to the optimal implementation mode and do not constitute a limitation on the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts shall be within the protection scope of the present invention.

Claims

1. A formal perovskite solar cell with rubidium acetate doped electron transport layer, characterized in that: It comprises FTO conductive glass, on which an electron transport layer, a doped electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode layer are sequentially deposited; the electron transport layer is a tin dioxide (SnO2) layer prepared by a water bath deposition method; the second electron transport layer is a thin film prepared by doping rubidium acetate small molecules in a tin dioxide (SnO2) aqueous solution and subjecting the solution to spin coating annealing.

2. The perovskite solar cell according to claim 1, characterized in that: The material of the perovskite light absorbing layer is FA x MA 1-x PbI3, where 0 <x<1。 3. The perovskite solar cell according to claim 1, characterized in that The hole transport layer comprises Spiro-OMeTAD, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 4-tert-butylpyridine (TBP).

4. A method for preparing a formal perovskite solar cell with a rubidium acetate-doped electron transport layer, characterized in that: The following steps are involved: Step 1, providing FTO conductive glass, and preparing an electron transport layer on the FTO conductive glass by a water bath deposition method; Step 2: preparing a doped electron transport layer on the electron transport layer by spin coating, wherein the method is as follows: 2.

1. Add deionized water to the tin dioxide aqueous dispersion, mix and dilute, and oscillate to evenly mix the two to obtain a tin dioxide aqueous solution A; wherein the tin dioxide aqueous dispersion: deionized water = 5:1; 2.

2. Adding rubidium acetate as a dopant to the tin dioxide aqueous solution A to obtain tin dioxide aqueous solution B; the concentration of the added rubidium acetate is 0.5-3 mg / mL; 2.3, spin coating the tin dioxide aqueous solution B on the electron transport layer obtained in step 2, the spin coating speed is 3000-5000 rpm, the time is 30-40 s, and annealing is carried out at a temperature range of 120-150° C. for 30-40 min to obtain a doped electron transport layer; Step 3, respectively preparing a lead iodide precursor solution and a mixed organic salt solution, and sequentially spin-coating the lead iodide precursor solution and the mixed organic salt solution on the doped electron transport layer using a two-step spin coating method, and annealing to obtain a perovskite light absorbing layer; Step 4: Spin-coat the hole transport layer on the perovskite light-absorbing layer, deposit the metal electrode, and obtain a formal perovskite solar cell with a rubidium acetate-doped electron transport layer.

5. The preparation method according to claim 4, characterized in that: The method for preparing the electron transport layer on the FTO conductive glass by water bath deposition in step 1 is as follows: 1.

1. Prepare solution C by mixing 1.25 mL of HCl solution, 25 ul of thioglycolic acid (TGA), and 100 ml of deionized water; 1.

2. Add 1250 mg urea and 275 mg SnCl2·2H2O to the solution C obtained in step 2.1 to obtain solution D; 1.

3. Immerse the FTO glass obtained in step 1 in solution D obtained in step 2.2 and heat in an oven at 90°C for 4 hours; 1.

4. The FTO glass with water-bath deposited SnO2 obtained in step 2.3 was cleaned in an ultrasonic oscillator with deionized water for 10 minutes, dried and placed on a hot plate at 170°C for 60 minutes to obtain an electron transport layer.

6. The preparation method according to claim 5, characterized in that: The implementation method of step 3 comprises the following steps: 3.

1. Add a mixed solvent to lead iodide, wherein the mixed solvent is composed of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 9:

1. Heat and stir at 60-80°C until dissolved to prepare a lead iodide precursor solution; 3.

2. Weigh 180-184 mg FAI, 12.8 mg MAI, and 9-9.5 mg MACL and dissolve them in 1 mL isopropanol to prepare a mixed organic salt solution; 3.

3. Spin-coat the prepared lead iodide precursor solution onto the obtained doped electron transport layer at a rotation speed of 1200-1800 rpm for 30 s, and anneal at 70°C to obtain a lead iodide film; spin-coat the prepared mixed organic salt solution onto the obtained lead iodide film at a rotation speed of 1800-2000 rpm for 30 s, and then transfer it to an environment with a relative humidity of 30%-40%, and anneal at 150°C to obtain a perovskite light absorbing layer.

7. The preparation method according to claim 5, characterized in that: The method for preparing the hole layer in step 4 is as follows: 4.

1. Weigh 500-520 mg of LiTFSI and add 1 mL of acetonitrile. Stir at room temperature until dissolved to prepare a LiTFSI solution. 4.

2. Weigh 70-75 mg of Spiro-OMeTAD, add 1 mL of chlorobenzene and 25-30 uL of TBP and 15-18 uL of the LiTFSI solution obtained in step 4.1, and stir at room temperature until dissolved to prepare a Spiro-OMeTAD solution; 4.

3. Spin-coat the Spiro-OMeTAD solution obtained in step 4.2 onto the perovskite light-absorbing layer at a rotation speed of 3000-5000 rpm for 30-40 seconds to obtain a hole transport layer.

Citation Information

Patent Citations

  • Trihydrate lead acetate doped perovskite solar cell and preparation method thereof

    CN107369764A

  • Preparation method and application of potassium bromide doped perovskite film

    CN113193120A

  • N-chlorosuccinimide-doped tin dioxide electron transport layer, perovskite solar cell and preparation method of perovskite solar cell

    CN116867342A

  • Doped perovskite thin film, preparation method thereof and perovskite solar cell

    CN117202750A

  • Preparation method for photovoltaic device based on stannic oxide transport layer, and use thereof

    WO2022057186A1